The impact of air transport services on the level of loyalty of passengers - Dedić, Samira; Mujić, Ermin; Puška, Adis (Oeconomica Jadertina, 2021)
The overall aim of this research is to determine the intensity and direction of the influence of air transport on the level of loyalty of tourist travellers. Four working hypotheses of the research were tested and analysed in detail. The empirical research was conducted on the basis of the collection of primary data by field research, using, using a highly structured survey questionnaire as a data collection form thereby. Likert scale with five levels of agreement was used in the survey questionnaire. The respondents were users of air transport services in Bosnia and Herzegovina. The research was conducted at two international airports; Sarajevo and Tuzla. It covered four low-cost airline companies, specifically Wizz Air, Pegasus Airlines, German wings and Norwegian Air Shuttle. In order to answer the set research questions related to the intensity study and the direction of air transport influence on the level of loyalty of tourist passengers, different ways and methods of data processing were used, all in accordance with the established research problems.